2015
DOI: 10.1039/c5ra00384a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of hybrid magnetic HKUST-1 and its highly efficient adsorption performance for Congo red dye

Abstract: A hybrid magnetic metal–organic framework HKUST-1 synthesized via chemical bonding approach possesses efficient and recyclable adsorption performance for Congo red.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…Figure 2b shows the decoration of Fe 3 O 4 -NHSO 3 H on HKUST-1, according to the report by Yan Xu et al, [29] suggesting that the decoration of Fe 3 O 4 -NHSO 3 H on HKUST-1 has not affected the physical characteristics of the MOF, which means the structure of HKUST-1 was well maintained after the modification. Figure 2b shows the decoration of Fe 3 O 4 -NHSO 3 H on HKUST-1, according to the report by Yan Xu et al, [29] suggesting that the decoration of Fe 3 O 4 -NHSO 3 H on HKUST-1 has not affected the physical characteristics of the MOF, which means the structure of HKUST-1 was well maintained after the modification.…”
Section: Batch Adsorption Experimentssupporting
confidence: 69%
See 1 more Smart Citation
“…Figure 2b shows the decoration of Fe 3 O 4 -NHSO 3 H on HKUST-1, according to the report by Yan Xu et al, [29] suggesting that the decoration of Fe 3 O 4 -NHSO 3 H on HKUST-1 has not affected the physical characteristics of the MOF, which means the structure of HKUST-1 was well maintained after the modification. Figure 2b shows the decoration of Fe 3 O 4 -NHSO 3 H on HKUST-1, according to the report by Yan Xu et al, [29] suggesting that the decoration of Fe 3 O 4 -NHSO 3 H on HKUST-1 has not affected the physical characteristics of the MOF, which means the structure of HKUST-1 was well maintained after the modification.…”
Section: Batch Adsorption Experimentssupporting
confidence: 69%
“…[30] Vibrations belong to Si-OH and Si-H at 996 cm −1 indicated to the bonding of TEOS to the MNPs. [28] For Fe 3 O 4 -NHSO 3 H@H-KUST-1 (Figure 3b), in addition to the peaks that are related to Fe 3 O 4 @SiO 2 -NHSO 3 H, the asymmetric stretching vibration at 2927 cm −1 was attributed to the aromatic ring C-H in H3BTC, the absorption peaks of the C O bonds (1633 cm −1 ), and the stretching vibration peaks of C C bonds on the benzene ring (1442 and 1373 cm −1 ) [29] were observed, indicating the formation of the surface of HKUST-1. [31] The peaks at 1217 and 1124 cm −1 are due to the sulfonyl moiety.…”
Section: Batch Adsorption Experimentsmentioning
confidence: 96%
“…Therefore, the treatment of wastewater is one of the highest‐ranking global environmental challenges in sustainable development. Different procedures have been developed for organic dye removal from industrial wastewater including adsorption, coagulation/flocculation, bacterial action, membrane filtration, ion exchange and electrochemical techniques . Among these methods, the adsorption technique is considered to have low capital investment as well as being a conventional and effective method .…”
Section: Introductionmentioning
confidence: 99%
“…Few studies about dye adsorption on HKUST‐1 have been reported and are summarized in Table . Nevertheless, the subtle aqueous stability reported for HKUST‐1 alone, has been employed for interactions with various types of dyes such as Congo red, Methylene blue, Crystal violet, Basic Fuchsin and Eriochrome black T with interesting results in their experimentations, as can be seen in Table . Moreover, HKUST‐1 in combination with other materials has provided an important strategy for generating long lasting composites in liquid (aqueous) phase.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, HKUST‐1 in combination with other materials has provided an important strategy for generating long lasting composites in liquid (aqueous) phase. In this line, Xu et al . used Fe 3 O 4 magnetic particles surface functionalized with SiO 2 ⋅NH 2 , to develop core–shell Fe 3 O 4 @SiO 2 systems, in combination with HKUST‐1 seeds to provide magnetic materials.…”
Section: Introductionmentioning
confidence: 99%